Pengaruh Inovasi Produk Dan Product Quality Terhadap Peningkatan Loyalitas Konsumen Pada Tiny Kitchen Medan - Boni Akbar Alfath Pohan; Ainun Mardhiyah; Onan Marakali Siregar (GLOBAL SCIENTS PUBLISHER, 2025)
The increasingly tight competition in the culinary business in the current era makes consumer loyalty one of the keys to business sustainability. Tiny Kitchen Medan, a food business specializing in dimsum mentai, cookies, and cheesecake, is required to continuously innovate and maintain product quality to retain its customers. Product innovation and product quality are believed to influence the level of consumer loyalty toward the brand. This study aims to identify and analyze the effect of product innovation on consumer loyalty, the effect of product quality on consumer loyalty, as well as the simultaneous effect of both variables on consumer loyalty at Tiny Kitchen Medan. This research employs a quantitative approach with an associative research type. Data collection was carried out by distributing questionnaires to 100 respondents who are consumers of Tiny Kitchen Medan. The data analysis techniques used include validity test, reliability test, multiple linear regression, t-test, F-test, and the coefficient of determination (R²). The results show that both product innovation and product quality have a partial and simultaneous influence on customer loyalty. The partial significance test (t-test) shows that the product innovation variable (X1) has a t-value of 2.557 > 1.985 with a significance level of 0.012 < 0.05 and a positive regression coefficient of 0.223. This indicates that product innovation (X1) has a significant influence on customer loyalty (Y). The product quality variable (X2) has a t-value of 7.992 > 1.985 with a significance level of 0.000 < 0.05 and a positive regression coefficient of 0.480, indicating that product quality (X2) significantly affects customer loyalty (Y). Based on the coefficient of determination test, the correlation value (R) between product innovation (X1), product quality (X2), and consumer loyalty (Y) is 0.893. Furthermore, the adjusted R square value shows that product innovation (X1) and product quality (X2) influence consumer loyalty (Y) by 79.3%, while the remaining 10.7% is influenced by other factors outside this research model.